A Narrative Inquiry: Students Perception in Increasing Teachers’ Identity By Join Microteaching - Setiyorini, Febri Ayu; Prihatin, Yoga; Santoso, Masfuad Edi (South Asian Journal of Social Sciences and Humanities, 2021)
Teaching is the process of focusing on people’s needs, experiences, and feelings. It makes the students learning new things for their future. Microteaching can be one of ways to help the students of teacher training and education to improve their teaching skills to be suitable with required qualifications and building up their teachers’ identity. This research aims to know what the students of the 8th semester English Department’s perceptions on microteaching related to their teaching practicum by using questionnaire and interview. Testing the validity and reliability of questionnaire uses correlation product moment SPSS. From fifteen questions, one question is invalid. Meanwhile, the results of this research are students of 8th semester English Department agree that microteaching is effective to build up their teaching competences and ability.